Reduced Blood RGS2 Expression in Mild Cognitive Impairment Patients - Milanesi, Elena; Cucos, Catalina Anca; Matias-Guiu, Jordi A.; Piñol-Ripoll, Gerard; Manda, Gina; Dobre, Maria; Cuadrado, Antonio (Frontiers in Aging Neuroscience, 2021)
Regulator of G protein signaling 2 (RGS2) is a gene involved in neuronal plasticity and synaptic signaling, whose expression in the brain is altered in neuropsychiatric and neurodegenerative disorders. Microarray data from large datasets suggested reduced RGS2 mRNA levels in the post-mortem brain tissue and blood of Alzheimer’s disease (AD) patients. The results were previously confirmed by quantitative real-time polymerase chain reaction (qRT-PCR) only ex vivo in lymphoblastoid cell lines derived from AD patients and controls. In this study, we compared RGS2 mRNA levels in peripheral blood samples from 69 mild cognitive impairment (MCI) patients to 50 age- and sex-matched non-cognitively impaired controls, out of which 25 patients were monitored at one year. We found that RGS2 was indeed downregulated in the peripheral blood of these patients (FR = -1.60, p < 0.001), and despite disease-specific therapy, RGS2 transcript levels continued to decrease at one year. The results suggest that RGS2 seems to be involved in AD pathology and progression and can be introduced in a panel of blood AD biomarkers.